Anti-MRSA Activities of Enterocins DD28 and DD93 and Evidences on Their Role in the Inhibition of Biofilm Formation - Al Atya, Ahmed K.; Belguesmia, Yanath; Chataigne, Gabrielle; Ravallec, Rozenn; Vachée, Anne; Szunerits, Sabine; Boukherroub, Rabah; Drider, Djamel (Frontiers in Microbiology, 2016)
Methicillin-resistant Staphylococcus aureus (MRSA), along with other antibiotic resistant bacteria, has become a worrisome superbug worldwide. This work was aimed at studying the efficacies of two class IIb bacteriocins, enterocins DD28 and DD93, against MRSA-S1 grown in planktonic culture and embedded in biofilms. These bacteriocins were purified, from the cultures supernatants of Enterococcus faecalis 28 and 93, using a simplified purification procedure consisting in a cation exchange chromatography and a reversed-phase high-performance liquid chromatography. The anti-Staphylococcal activity of these bacteriocins was shown in-vitro by the assessment of the minimal inhibitory concentration (MIC). Afterwhich, a checkerboard and time-kill kinetics permitted unveiled a synergistic effect of these bacteriocins in combination with erythromycin and kanamycin against the clinical MRSA-S1. These bacteriocins alone or in combination with erythromycin and kanamycin were able to impede the formation of MRSA-S1 biofilms on stainless steel and glace devices as supported by the microbial cell counts, epifluorescence and Scanning Electron Microscope analyses.